Aristotle’s Concept Φρονησις and Moral Education (Annual of the Faculty of Philosophy in Skopje, 2018)
In the systematization of intellectual virtues, amongst which are knowledge (ἐπι-στήμη), wisdom (σοφία), understanding (νοῦς) and craft (τέχνη), Aristotle enumeratesthe practical wisdom (φρόνησις) and defines it as: “to be able to deliberate correctly aboutwhat is good and advantageous …, not partially… but about what sorts of things furtherliving well as a whole (Arist. NE 1140a25-27, trans. Reeve). Aristotle distinguishes φρόνη-σις from the knowledge and from the crafts because under this notion he presupposes theability not only to decide how to achieve a certain goal, but also the ability to deliberateand to determine good ends according to the aim of the individual in achieving its own happiness(εὐδαιμονία). In educational context, this presupposition entails the standpoint thateducation should not be understood only as a process of attaining knowledge and crafts, butalso as a process of becoming a virtuous person through thinking embedded in context.Without the pretension to give a consistent system of the principles of virtue ethics,concerning education, this article will inspect the possibility of laying out a differentperspective concerning educational practices that are deduced from an ancient ethical theory,especially the specific notion that this theory introduces, the notion of φρόνησις.
Keywords: ΦΡΟΝΗΣΙΣ; ARISTOTLE; VIRTUE ETHICS; MORAL EDUCATON